Comparative Study of Relative Peripheral Refraction in Children With Different Degrees of Myopia - Xiaoli, Lu; Xiangyue, Zheng; Lihua, Lian; Yuting, Huang; Chuni, Lin; Yujie, Xia; Zhao, Wang; Xiaoyi, Yu (Frontiers in Medicine, 2022)
Purpose To investigate the difference of peripheral diopter and its relationship with ocular biological parameters in adolescent patients with different degrees of myopia. Methods 90 adolescent myopic patients who met the enrollment requirements were examined with the automatic optometer after mydriasis. According to spherical equivalents (SE), the patients were divided into Emmetropia group (Group E, +0.5D